2007
DOI: 10.1136/bjo.2007.115501
|View full text |Cite
|
Sign up to set email alerts
|

Types of choroidal neovascularisation in newly diagnosed exudative age-related macular degeneration

Abstract: Aim: To describe the types and location of choroidal neovascularisation (CNV) in exudative age-related macular degeneration (AMD), including vascularised pigment epithelial detatchments (PED), and most recently described subtypes, such as retinal choroidal anasmostosis, also termed ''retinal angiomatous proliferation'' (RAP). Methods: Prospective multicentre consecutive descriptive case series. A total of 207 consecutive cases of newly diagnosed exudative AMD undergoing fluorescein angiography (FA) were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 20 publications
2
67
3
2
Order By: Relevance
“…8 The proportion of different types of angiographically identified lesions were similar in this study to other reported studies for populations showing occult lesions as the most common form identified angiographically for patients with wet AMD. 9,10 Cohen et al 9 found a total of 17.6% had classic CNV only, 5.4% and 8.3% had predominantly and minimally classic CNV, respectively, and 32.7% had occult CNV. RAP was observed in 15.1% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…8 The proportion of different types of angiographically identified lesions were similar in this study to other reported studies for populations showing occult lesions as the most common form identified angiographically for patients with wet AMD. 9,10 Cohen et al 9 found a total of 17.6% had classic CNV only, 5.4% and 8.3% had predominantly and minimally classic CNV, respectively, and 32.7% had occult CNV. RAP was observed in 15.1% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…3,14,15 This peculiar form of AMD is characterized by a high and cumulative risk of bilateralization, estimated to be as high as 40% after 1 year, 56% after 2 years, and 100% after 3 years. 16 ICG, by improving the imaging of choroidal circulation, is an invaluable diagnostic tool in such cases, showing typically a late focal area of intense hyperfluorescence described as a hot spot.…”
Section: Discussionmentioning
confidence: 99%
“…Acute visual loss can be caused by tears of the RPE layer, especially in combination with massive subretinal haemorrhages. 2,[11][12][13]28,29 Using ICG-A, different kinds of neovascularization could be identified that can be regarded as being responsible for serous PED. Occult CNV situated mostly at the margin can often be distinguished from centrally localized CNV on a RAP lesion.…”
Section: Discussionmentioning
confidence: 99%
“…This process can be accelerated by ruptures in the retinal pigment epithelium (RPE) layer and by subretinal haemorrhages. [7][8][9][10][11][12][13] Previously used therapeutic strategies such as photocoagulation or photodynamic therapy (PDT) have produced only unsatisfactory results. [13][14][15][16][17] The reasons for this include both the development of PED and CNV recurrences.…”
Section: Introductionmentioning
confidence: 99%